Seasonal succession of endophyte and the association with active ingredients in Rheum palmatum - Ni Li; YiFan Mao; YaLi Huang; LingXuan Zhang; Lu Hou; XiaoJun Liu; YaRong Du; DaWei Chen; Kun Sun (Microbiology Spectrum, 2024)
ABSTRACT The endophyte is closely related to medicinal plant growth and development, stress resistance, and active ingredients’ accumulation. However, a seasonal succession of endophytes and the association with active ingredients is still unclear. In this study, we used high-throughput sequencing methods to compare the endophyte diversity of Rheum palmatum under different seasons and analyze the association between endophytes and five active ingredients. The results show that the diversity of endophytic fungi increased and then decreased, while bacterial diversity increased with the change of season. Community composition showed that the dominant genera of endophytic fungi were different under the different seasons, while the dominant genera of endophytic bacteria were Delftia. Analysis of co-occurrence network maps showed that the connectivity and complexity of endophytic fungi and bacterial networks decreased with the change of season. Spearman analysis indicated that the active ingredients of R. palmatum were significantly positive correlation with genera of endophytic fungi (Chalara). FUNGuild and PICRUSt predictive analysis indicated that the function of endophytic fungi and bacteria, respectively, were symbiotroph and metabolism, and relative abundances were different under the different seasons. Our results help elucidate the mechanism of medicinal plant–endophyte interaction.IMPORTANCEThrough the investigation of the seasonal succession of endophytes and the association with active ingredients in Rheum palmatum, we found that the diversity and composition of endophytes in R. palmatum exhibited seasonal dynamics, and the active ingredients of R. palmatum showed a significantly positive correlation with the genus of endophytic fungi (Chalara). Our results may lay a foundation for understanding the interaction mechanism of endophyte and medicinal plant, and can also provide a theoretical basis for sustainable production of medicinal plants.